Mirrorless car: a feasibility study - Mohamed Ali, Jaafar Syed; F. Fatin, Bazilah (Trans Tech Publications Ltd., Switzerland, 2014)
Mirrorless cars are the conceptual cars in which the mirrors which are used as a visual aid for safe driving are replaced with camera and LCD screens thus making it totally mirrorless. These cars without mirror projections will result in clean external aerodynamics thereby reducing considerable amount of drag and hence offers a high potential to achieve higher fuel economy in driving a car. The present study is a trial to test whether such a mirrorless car can create a better driving condition for the driver in terms of ergonomics, safety and comfortability. Thus the latest modern technology is fused in a Malaysian car model making it mirrorless with the cameras replacing mirrors and the dashboard was modified to install the LCD screens on it. The modified car was tested for its characteristics on safety, comfortability and ergonomics. The driver’s behaviour while driving the mirrorless car was studied extensively and numerous interesting conclusions were derived.